ANALISIS AKIBAT DARI PEMALSUAN DOKUMEN PERKAWINAN DITINJAU BERDASARKAN UNDANG-UNDANG NOMOR 1 TAHUN 1974 DAN HUKUM ISLAM - Aufa Putri Nabila; Mia Hadiati (Fakultas Hukum Universitas Tarumanagara, 2022)
Every citizen has the right to marry because this marriage is a sacred event so that there are manylegal responsibilities. This is stated in Article 1 of Law Number 1 of 1974 concerning Marriage whichstates